2022
DOI: 10.2147/oajsm.s340702
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Graft Choice in Athletic Patients with Anterior Cruciate Ligament Injuries: Review and Clinical Insights

Abstract: Anterior cruciate ligament (ACL) rupture is a common sporting-related knee injury with a potentially detrimental impact on the athlete’s career, yet there is no formal consensus on the optimal graft choice for reconstructing the ruptured ACL in this specific population. Options for reconstruction include autograft, allograft, and artificial grafts. However, each has associated failure risk and donor site morbidity. Our operational definition of the athlete is a skeletally mature individual participating in hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 119 publications
0
6
0
1
Order By: Relevance
“…In ACLR, there are three options, including allografts, and artificial grafts and autografts [ 6 , 9 ]. Compared with the first two types of grafts, autologous tendons are removed from the patient's own body and therefore, do not cost extra for the grafts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In ACLR, there are three options, including allografts, and artificial grafts and autografts [ 6 , 9 ]. Compared with the first two types of grafts, autologous tendons are removed from the patient's own body and therefore, do not cost extra for the grafts.…”
Section: Discussionmentioning
confidence: 99%
“…Graft selection is an important step affecting the prognosis of ACLR, and an ideal graft is associated with good postoperative rehabilitation, return to a full sporting function, and few complications [ 7 , 8 ]. Current options include autografts, allografts, and artificial grafts [ 6 , 9 ]. However, there is no consensus on the best graft for ACLR [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…8 Current evidence suggests the use of allografts in specific circumstances such as multiligament knee reconstructions, inadequate autograft tissue, or in older, less active populations. 9 The theoretical advantages of allografts are: elimination of donor site morbidity, less pain, shorter surgical and rehabilitation times and better cosmetic results. 10 Krych et al 11 reported a fivefold higher risk of rerupture in cases that used an allograft.…”
Section: Autograft Versus Allograftmentioning
confidence: 99%
“…8 Evidência atual sugere o uso de aloenxertos em circunstâncias específicas como reconstruções multiligamentares do joelho, tecido inadequado de autoenxerto ou em populações mais idosas e menos ativas. 9 As vantagens teóricas dos aloenxertos são: eliminação da morbidade do sítio doador, menos dor, tempos cirúrgico e de reabilitação menores e melhor resultado cosmético. 10 Krych et al 11 relataram um risco cinco vezes maior de reruptura em casos que utilizaram aloenxerto.…”
Section: Autoenxerto Versus Aloenxertounclassified
“…In terms of improved joint biomechanics, comparable performances have been evidenced for bioinert (titanium-based and non-degradable thermoplastic-based) [ 11 , 12 ], biodegradable (magnesium-based and bioglass-based) [ 13 , 14 ], and bioabsorbable (biopolyester-based and biopolyester/calcium phosphate-based) [ 15 , 16 ] interference devices. Also, common side effects have been reported following the long-term use of such devices, including joint effusion, intra-articular screw migration, screw fragmentation or rupture, local inflammation, and infection [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%